The Relationship Between the Use of Digital Flashcards on Quizlet and English Vocabulary Mastery in Elementary School Students - Aswita, Mila; Moetia, Meristika (International Journal of Language Teaching and Education, 2025)
This research investigates the correlation between the utilization of digital flashcards on the Quizlet platform and the Mastery of English vocabulary among elementary school students. The study focused on thirty-fifth-grade students enrolled at Elementary School 6 in Aceh Barat Daya, selected through purposive sampling to ensure relevance to the research objectives. To gather the required data, researchers employed two instruments: a vocabulary test designed to assess students' Mastery of English vocabulary, and a questionnaire developed to measure the extent of Quizlet usage among participants. Before performing statistical analysis, the data were first tested to confirm that the assumptions of normality and linearity were met. Once these conditions were satisfied, the Pearson product-moment correlation technique was applied to analyze the relationship between the two variables. The findings revealed a strong and statistically significant positive correlation (r = 0.712, p < 0.001), suggesting that the more frequently students used Quizlet, the higher their vocabulary scores tended to be. It implies that the integration of digital flashcards through platforms like Quizlet can serve as an effective strategy to enhance vocabulary acquisition among learners at the elementary level. Consequently, the study supports the idea that incorporating digital learning tools into classroom instruction can contribute meaningfully to language learning outcomes, particularly in vocabulary development.